The Implementation of Sharī‘ah Governance Framework and Change in Performance of Islamic Banks in Pakistan : Implementation of Sharī‘ah Governance Framework - Bukhari, Syed Muhammad Hassan Bukhari; Khan, Dr. Mohammad Ayaz; Kalim, Dr. Rukhsana Kalim (Al-Irfan, 2022)
The survival of the Islamic banking system depends on Sharī‘ah compliance and profitability. The profitability is linked with the good performance of Islamic banks. A number of studies are evident of the role of Sharī‘ah governance on the performance of Islamic banks. This paper aims to check the change in financial performance in the pre (2011-2014) and post (2016-2019) implementation of the Sharī‘ah Governance Framework. This study follows a positivistic approach and uses quantitative methods. Descriptive statistics are used to get a clear picture of the data. The paired sample t-test was used to analyze the data available in financial statements. The finding reveals that the financial performance of Islamic banks has a decreasing trend from pre (2011-2014) and post (2016-2019) data analysis. This study is one of its kind to see the change in the financial performance of Islamic banking institutions in pre-and post-implementation of the Sharī‘ah Governance Framework in Pakistan.